Unraveling the relationship between the DRPs with PANNS and extrapyramidal symptoms in schizophrenia: Implications for antipsychotic therapy - Solihah, Riyadatus; Anggraeni, Novi; Purwanta, Purwanta (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
Schizophrenia is a severe and chronic mental disorder that requires long-term antipsychotic therapy. However, the use of these medications is often accompanied by drug-related problems (DRPs), which affect the effectiveness of treatment and increase the risk of health complications. Objective: This study aims to evaluate the relationship between DRPs and therapy outcomes in schizophrenia patients at Syamrabu Bangkalan Hospital. Methods: A cross-sectional design with a retrospective method was used in this study. The sample was selected through purposive sampling from patients diagnosed with mental disorders who were using antipsychotic drugs. The PANSS scores and the frequency of extrapyramidal events were assessed to evaluate therapy outcomes. The data analysis was conducted using statistical correlation tests. Results: Among the 110 patients studied, 200 cases of DRPs were found, with drug interactions being the most common (42.5%). Correlation analysis showed a significant relationship between the number of drugs consumed and the number of DRPs (p=0.000, r=0.352). However, no significant association was found between the number of DRPs and patient therapeutic outcomes (p=0.340, r=-0.076). Combining atypical and typical antipsychotics proved more effective in reducing PANSS scores and demonstrating a lower risk of extrapyramidal side effects compared to monotherapy. Conclusion: An increase in the number of medications taken by a schizophrenia patient correlates with a higher incidence of DRPs. Therefore, close monitoring and pharmaceutical interventions are needed to optimize therapy and reduce the risk of side effects and complications.